Cooperative Learning Based on Word-Matching Game to Enhance Mastery of Arabic Vocabulary for Eighth-Grade MTs Students - Fauziyah Nurul Hanifah; Maman Abdurrahman; Tatang; Shofa Musthofa Khalid; Azra Adrina Langguly (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
The research addresses the necessity for developing and implementing more effective learning methods and media to enhance the mastery of Arabic vocabulary among school students. The research aims to apply and evaluate the effectiveness of cooperative learning through the word-matching game technique to enhance the mastery of Arabic vocabulary among grade VIII students. This research used a quantitative approach with a quasi-experimental design, specifically a non-equivalent control group design. The research sample consisted of two VIII classes in MTs Negeri 1 Bandung City, namely the control class (VIII B) and the experimental class (VIII E), each totaling 30 students. Data were collected through observations, interviews, and tests to measure the enhancement of Arabic vocabulary mastery. The results showed that cooperative learning with word-matching game technique significantly enhanced students' vocabulary mastery compared to the conventional method. The experimental class showed significant enhancement with a normalized gain score of 56.55%, categorized as quite effective. In comparison, the control class only obtained a score of 30.50%, which is classified as ineffective. The scientific contribution of this research is to provide empirical evidence regarding the effectiveness of game-based cooperative learning in enhancing Arabic vocabulary acquisition at the junior high school level. This research also enriches the literature on innovative learning methods in language education, especially Arabic. Future research suggests further studies exploring the application of this word-matching game technique at different educational levels and contexts and examining the long-term effects of using this technique. In addition, further research can consider other factors that can affect learning success, such as student motivation, parental involvement, and technological support in the learning process.